THE TRADITION OF BUWUHAN : BETWEEN SOCIAL COHESION, ALMS, AND COMMERCIALIZATION - Sardjuningsih (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2020)
The buwuhan tradition has for hundreds of years been a means of social cohesion in rural communities. In social relations, buwuhan can be conceived of as economic negotiations using an exchange approach. As a subculture, buwuhan becomes a strategic tool in marking the stages of one’s life, which is held at weddings and circumcisions. In rural communities this economic exchange is organized through record keeping. Awareness of social norms of negligence requires that the exchange value be paid back at a minimum. In the modern era, the buwuhan tradition experiences a value shift, making the buwuhan tradition a means of taking personal advantage, which is wrapped in the values of solidarity and harmony. Especially in urban communities and societies undergoing social transformation such as sub-urban communities. This is because modernization has changed the way people look at the value of money. This meaning has further led to the occurrence of abusive practices that have been implemented improperly, forced, exploited, with modes and strategies for material gain. To preserve the value of the buwuhan tradition, there must be a social reconstruction that returns the meaning of this tradition into its function as a social cohesion that can be accepted by the norms of modern society, which are more rational, realistic, interactive, familiar, and harmonious.